Hubungan Servant Leadership dengan Komitmen Organisasi pada Pengurus Bank Sampah Kabupaten Bantul - Anisa Zakiatun Nufus; Arundati Shinta; Ayu Gigih Rizqia (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to empirically determine the relationship between servant leadership and organizational commitment among waste bank managers in Bantul Regency. This study uses a quantitative approach with a sample of 46 waste bank managers selected through probability sampling using stratified random sampling techniques. Data analysis was performed using Pearson Product Moment correlation. The results revealed a correlation coefficient of 0.515 with a significance value of 0.000 (p <0.01), indicating a positive and significantrelationship between servant leadership and organizational commitment. Additionally, the coefficient of determination was 0.265, meaning that servant leadership contributes 26.50% to organizational commitment